Planar‐biaxial low‐cycle fatigue behavior of the nickel‐base alloy Inconel 718 at elevated temperatures under selected loading conditions. Issue 6 (24th February 2022) - Böcker, Marco; Babu, Harish Ramesh; Henkel, Sebastian; Raddatz, Mario; Gampe, Uwe; Biermann, Horst
Abstract: The isothermal planar‐biaxial fatigue behavior was studied for two different disk batches of nickel‐base superalloy Inconel 718 using cruciform specimens at 400°C and 630°C under equi‐biaxial and shear loading. Additionally, non‐proportional tests were performed. The planar‐biaxial test results were compared with uniaxial reference tests using the von Mises equivalent strain hypothesis, a shear strain parameter of the critical plane, and a modified crack‐opening‐displacement strain range approach. Additionally, the crack initiation mechanism was analyzed. Using a modified crack‐opening‐displacement strain range approach, the low‐cycle fatigue lifetimes of the proportional planar‐biaxial tests (i.e., lifetimes up to 40, 000 cycles) were described within a scatter band of two. Thus, it was better than using the equivalent strain of von Mises or a shear strain parameter. The fatigue crack initiation took place at oxidized primary carbides at the surface. The crack paths were presented. Highlights: IN718 showed cyclic softening and final stabilization, also for planar‐biaxial loading. A modified COD strain range approach showed a good correlation in the LCF regime. Crack initiation occurred on the surface at oxidized primary carbides in the gauge area. The crack paths were monitored for the different planar‐biaxial loading conditions.